Technology Transfer, Foreign Direct Investment and Economic Growth: A Comparative Analysis of Asian and African Economies - Awolusi, Olawumi Dele (2008)
This paper evaluates the intensity of international technology transfer in selected Asian and African economies through import of machinery and FDI from 1970 to 2006; it also investigates the long-run equilibrium relationships among the international factors and economic growth, as well as, assessing the short-term impact of inward FDI, trade and economic growth on international technology transfer to the selected countries. This research revealed that, the technology transfer intensities across the selected countries vary substantially, with Malaysia leading in attracting FDI, both in quantity and quality of diffusing most modern technological knowledge and skills, among the three selected countries, followed by Thailand, and Nigeria. A multivariate cointegration technique developed by Johansen & Juselius (1990) was employed to investigate the long-run equilibrium relationships among the international factors and economic growth. The results of the analysis affirmed the existence of cointegrating vectors in the systems of these countries during the study period. While the variables in Malaysia and Thailand models have a long-run equilibrium relationship with one another and were adjusting in the short-run via three identified channels, the variables in the system of Nigeria did the same adjustment through four channels (Lee and Tan, 2006). Furthermore, since the existence of cointegrating vectors (cointegration) in the system of a countries only presumed the presence or absence of Granger-causality, which does not indicate the direction of causality between the variables, hence, the short-term impact of inward FDI, trade and economic growth on international technology transfer to the selected countries was tested via Granger Causality test based on Vector Error-Correction Model. The results of the test revealed a short-run causal effect either running unidirectionally or bidirectionally among the variables for each country. Finally, all the variables in the systems of the selected countries were adjusting to equilibrium in the long run, with the exception of domestic investment (DI) in both Malaysian and Nigerian systems, which failed to do the adjustment in the long run.